Gender Gaps in Ecuador : An Overview - World Bank (World Bank, Washington, DC, 2019)
This review of gender issues aims to uncover the main gender gaps in the country, and to identify potential policy recommendations that could help closing them in the coming years. The note is an input to the development of a Gender Action Plan for the Andean Countries under the Gender Analysis Work Program.The note lays out a descriptive overview of gender gaps in endowments, economic opportunities and agency – the explanation of the observed situation is outside the scope of this note.The note applies the analytical framework devised by the WDR 2012 on Gender Equality and Development. Chapter one covers the legal and institutional framework and the issue of the agency of women – e.g. political representation and violence against women, time use, and attitudes towards women; Chapter two provides an overview the situation with regards to the main endowments of health and education; and Chapter three deals with the existing gender gaps in economic opportunity labor force participation and unemployment, the quality of employment, earnings, entrepreneurship and access to finance.The review presented here is the result of the first stage in the assessment process.This note mainly reflects an initial descriptive exercise, and will be revised after the completion of stakeholder consultations in the countries; the results of such consultations will not only help identify additional literature and research on specific issues, but also help prioritize the key gender gaps to be addressed based on the way discussions on the issue are currently taking place in the country.